1997
DOI: 10.1016/s1010-7940(96)01122-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of Duraflo® II heparin treated extracorporeal circulation circuits (2nd version) The European working group on heparin coated extracorporeal circulation circuits

Abstract: These findings suggest that improved recovery can be expected with heparin treated circuits in specific higher risk patient populations (e.g. females) and when prolonged aortic cross clamp time is anticipated. Further investigations are recommended to analyses the clinical benefit of heparin treated circuits in studies with patients in different well defined risk categories and under better standardised circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 24 publications
(27 reference statements)
1
18
1
3
Order By: Relevance
“…Our results concerning postoperative bleeding are indirectly supported by comparative studies where patients treated with noncoated circuits serve as a control group. Reduced bleeding and transfusion requirements have repeatedly been reported where a lower dose of heparin is given, 5‐8 whereas no significant effects on bleeding have been demonstrated in larger studies including full heparin dose 12‐14 . In the present study, we were not able to demonstrate any reduction in allogeneic transfusions.…”
Section: Discussioncontrasting
confidence: 66%
“…Our results concerning postoperative bleeding are indirectly supported by comparative studies where patients treated with noncoated circuits serve as a control group. Reduced bleeding and transfusion requirements have repeatedly been reported where a lower dose of heparin is given, 5‐8 whereas no significant effects on bleeding have been demonstrated in larger studies including full heparin dose 12‐14 . In the present study, we were not able to demonstrate any reduction in allogeneic transfusions.…”
Section: Discussioncontrasting
confidence: 66%
“…Indeed, a clinical study showed a decreased intrapulmonary shunt with improved respiratory index (PO 2 /FiO 2 ) after CPB by using heparin-coated circuits, although intubation time and ICU stay were not affected [35]. Others, using a scoring-system based either on intubation time, the central-peripheral temperature difference, the postoperative fluid balance, and on various adverse effects after CABG, showed a significantly positive clinical effect in patients treated with heparin-coated circuits, and especially in patients with cross-clamp times exceeding 60 min [16,36]. De Vroege et al [31] demonstrated comparatively significant postoperative differences in favour of the patients treated with heparin-coated circuits in terms of the pulmonary shunt fraction, the pulmonary vascular resistance index, and the PaO 2 /FiO 2 ratio, as well as various inflammatory markers reflecting complementary activation.…”
Section: Methodology and Strategy For Management Of Lung Dysfunction mentioning
confidence: 99%
“…The European Working Group on heparin-coated circuits failed to show any clinical benefit in a multicenter randomized controlled trial of heparin-coated circuits (Duraflo II) versus standard circuits with identical heparin in lowrisk patients [50]. However, a separate multicenter randomized controlled trial in a group of high-risk patients demonstrated decreased ICU and hospital lengths of stay, as well as decreased incidence of postoperative lung and kidney dysfunction in patients undergoing CPB with the Duraflo II circuit as compared with a noncoated circuit, both with standard heparin doses [51].…”
Section: Clinical Results With Heparin-coated Circuits In Cardiopulmomentioning
confidence: 99%